Immunogenicity and Complications of the Pentavalent Vaccine in Iranian Children - Ekrami Noghabi, Mina; Saffar, Mohammad Jafar; Rezai, Shaghayegh; Saffar, Hana; Saffar, Hiva; Hosseinzadeh, Fatemeh; Nadi Ghara, Aliasghar; Rezai, Mohammad Sadegh (Frontiers in Pediatrics, 2021)
Objective: Vaccination is one of the most convenient and safe preventive care measures available for children. The Pentavalent vaccine which protects against five major infections including diphtheria, tetanus, pertussis, hepatitis B(HepB) and Haemophilus influenzae type b(Hib) was added to the Iranian national immunization program in November 2014. This study aimed to determine the Pentavalent vaccine adverse events and immunogenicity in an Iranian children population in Sari, northern Iran. Method: In this descriptive-analytical study, children who were vaccinated with three doses of the Pentavalent vaccine were studied. Two venous blood samples were obtained before the first dose and 4 weeks following the last booster dose. Possible local and systemic complications of the vaccine were recorded until 7 days following vaccination. Antibody titers were measured by quantitative ELISA kits and geometric mean titer(GMT) was calculated for each vaccine component before and after 3 doses of vaccine. Statistical analysis was performed by SPSS 20.0 software and Chi-square and Fisher’s exact tests were used for analysis. Results: Immunogenicity of the Pentavalent vaccine for tetanus was 100%(GMT:2.52 Eu/mL, 95%CI: 2.22-2.88), Hib 98.7%(GMT:2.44 Eu/mL, 95%CI: 2.06-2.89), HepB 98.7%(GMT:153.54 Eu/mL, 95%CI: 133.73-176.29), diphtheria 93.1%(GMT:0.43 Eu/mL, 95%CI:0.37-0.51) and pertussis were 63.7% (GMT:19.44 Eu/mL, 95%CI:16.42-23.03). The most common systemic complication after vaccination was fever. Also, one infant cried for more than 3 hours after the second dose. Other serious side effects were not observed. Conclusion: The Pentavalent vaccine used in Iran can cause adequate antibody response against diphtheria, tetanus, pertussis, Hib and hepatitis B in most cases with minimal side effects. The immunogenicity of this vaccine is significantly lower for pertussis. In this study, no severe complication leading to contraindication to subsequent injections was reported. So, the present policy in replacing triple DTP vaccine with Pentavalent vaccine should be continued in Iran.